2014
DOI: 10.5125/jkaoms.2014.40.4.155
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factor on the prognosis of arthrocentesis

Abstract: ObjectivesThe purpose of this article is to evaluate factors influencing prognosis of arthrocentesis in patients with temporomandibular joint (TMJ) disorder.Materials and MethodsThe subjects included 145 patients treated with arthrocentesis at the Dental Center of Ajou University Hospital from 2011 to 2013 for the purpose of recovering mouth opening limitation (MOL) and pain relief. Prognosis of arthrocentesis was evaluated 1 month after the operation. Improvement on MOL was defined as an increase from below 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Similarly, Kim et al found that the success rate of arthrocentesis in patients in their fifties or older is likely to be low. Their results were consistent with the previous studies of Von Korff et al and Attia et al On the contrary, Nishimura et al found no significant relationship between the age and the success rate of the arthrocentesis . Consistent with the Nishimura et al, we found no correlation between the age and the success of the procedure.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Similarly, Kim et al found that the success rate of arthrocentesis in patients in their fifties or older is likely to be low. Their results were consistent with the previous studies of Von Korff et al and Attia et al On the contrary, Nishimura et al found no significant relationship between the age and the success rate of the arthrocentesis . Consistent with the Nishimura et al, we found no correlation between the age and the success of the procedure.…”
Section: Discussionsupporting
confidence: 93%
“…Studies show that bruxism is more common among TMD patients than in healthy subjects . Parafunctional habits were also found to be a prognostic factor that influences the outcome of arthrocentesis . Kim et al suggested that patients with parafunctional habits are more likely to fail after an arthrocentesis procedure .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations